DIGITAL WORKFLOW FOR THE CORRECTION OF A GUMMY SMILE - Jevremović, Ana Radojica; Jevremović, Danimir (Acta medicae Medianae, 2026)
Excessive gingival display during smiling, known as a “gummy smile,” can negatively affect a patient’s aesthetic appearance and self-confidence. The digital workflow for correcting this condition involves the use of technologies such as intraoral scanning, Cone Beam Computed Tomography (CBCT) diagnostics, and Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) systems for the fabrication of surgical guides. This paper presents a clinical case in which a digital protocol was used to plan and execute gingivoplasty with the aid of a surgical guide. The results demonstrated high precision, minimal invasiveness, and predictable aesthetic correction. The application of digital technologies enhances communication with patients, reduces treatment time, and increases procedural safety, making it an effective approach in aesthetic dentistry.
Keywords: digital planning, Computer-Aided Design/Computer-Aided Manufacturing, gummy smile, gingivoplasty, surgical guide, aesthetics